Potential Embryogenic Callus Induction Protocol Through Cell Suspension Culture For High Frequency Plant Regeneration Of Maspine Pineapple (Ananas comosus L.) - Bukhori, M.F. Mohamad; Khalid, Norzulaani; Ven, Ch'ng Lou (Borneo Journal of Resource Science and Technology, 2016)
To explore the potential for embryogenic callus induction protocol through cell suspension culture for high frequency plant regeneration of Maspine pineapple (Ananas comosus L.), eight different culture media formulation were evaluated for their effects on the induction of somatic embryos from sucker explants. Explants were cultured on MS medium supplemented with various media concentration (NAA, Dicamba and BAP, Picloram, Kinetin and NAA, 2,4-D, TDZ, and TDZ and BAP). Embryogenic callus induction percentage, color and texture of the callus were assessed after five months of culture. The optimum medium for the proliferation of in vitro shoots from sucker explants was MS medium supplemented with 3 mg/L BAP. Meanwhile, the optimum medium for the induction of fastest and high percentage of embryogenic callus growth from in vitro leaf-based was MS medium supplemented with Picloram. Results of mean comparison showed that 3 mg/L Picloram were more effective on explants than 10 mg/L. Results of the double staining method proved that somatic embryogenesis occurred in MS supplemented with 3 mg/L Picloram. Under microscopic observations, the globular-stage of the embryos were revealed in callus cells which is relatively suitable for suspension cells inoculums, indicating that the tested PGR were significantly effective for somatic embryogenesis formation in this species. Most embryogenic callus from sucker explants was yellowish-mucilaginous-wet-friable. The developed protocol potentially leads to the production of embryogenic callus from sucker explants and plant regeneration through somatic embryogenesis.